Respon Morfofisiologi Tanaman Kelapa Sawit Pre Nursery pada Pemberian Kompos Kotoran Walet dan Bakteri Synechococcus sp. - Andrian Surya Kristanto; Rizky Anggoro; Danie Indra Yama; Jaini Fakhrudin; Muhammad Ali (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2022)
The purpose of this study was to determine the effect of swallow manure and Synechococcus sp. bacteria on the morphophysiology of oil palm plants in Pre Nursery. The experiment used a factorial Randomized Block Design (RAK) and three replication. The first factor being swallow manure compost, W0 = 0 grams/plant, W1 = 100 grams/plant, W2 = 150 grams/plant, W3 = 200 grams/plant. The second factor was concentration of Synechococcus sp. Bacteria, S1 = concentration 10 ml/L, S2 = concentration 15 ml/L, S3 = concentration 20 ml/L. Parameters observed were plant height, stem diameter, the number of leaves, total chlorophyll, stomata density, stomatal opening width, and transpiration rate. Application of swallow manure compost had a significant effect on the parameters of plant height, number of leaves and total chlorophyll. Concentration of Synechococcus sp. gave a significant effect on the parameters of the transpiration rate while on morphology there was no significant effect on all parameters. The best dose of compost for plant height was 200 g of compost and 10 ml/L of bacterial concentration, while the treatment of 200 g of compost and 15 ml/L of bacterial concentration was the best dose of total chlorophyll and stomatal density parameters. Combination treatment of swallow manure compost and Synechococcus sp. gave a significant effect on the parameters of plant height, total chlorophyll and stomatal density. Keywords: Morphophysiology, Organic Fertilizer, Pre Nursery, Palm Oil, Synechococcus sp